PROBLEMS OF LEGAL REGULATION OF PLEDGE EXCLUSIVE RIGHTS IN ARMENIA AND SOME PROBLEMS OF LENDING SECURED BY INTELLECTUAL PROPERTY IN THE RUSSIAN FEDERATION: залог исключительных прав - Tadevosyan, Lusine (State and Law, 2022)
In the article studied and characterized modern situation with the exception of exceptional powder. Consideration of the possibility and peculiarities of the conclusion of a pledge agreement in Armenia, where the subject of the pledge will be exclusive rights. On the basis of the study, the normative bases act, regularizing the pledge of exceptional rights, incurring some problems of lending under the pledge of exceptional rights to the objects of intellectual property possessed and proposed by the creditors.